Efficacy of photodynamic therapy on candida colonization and clinical symptoms in denture stomatitis: a systematic review and meta-analysis - Sadeq A. Al-Maweri; Mohammed Nasser Alhajj; Lamyia Anweigi; Sajna Ashraf; Esam Halboub; Nosizana Mohd Salleh; Rawan H. Alanazi; Mohammad Zakaria Nassani; Mohammed Noushad; Jumma O. Al Khabuli; Anas Shamala (BMC Oral Health, 2024)
Abstract Background Photodynamic therapy (PDT) has been recently proposed as a promising alternative therapy for Denture Stomatitis (DS). The present systematic review and meta-analysis investigated the current available evidence regarding the efficacy of PDT in the management of DS. Materials and methods PubMed, Scopus, Web of Science, Google Scholar, and ProQuest were searched up to June 7, 2023. All relevant clinical trials were included. RevMan software was used for the statistical analyses. Results Elven randomized clinical trials (460 DS patients) were included. Eight studies assessed the efficacy of PDT vs. topical antifungal therapy, while three studies assessed the adjunctive use of PDT (PDT + antifungal therapy) vs. topical antifungal therapy alone. The results revealed comparable efficacy of PDT and conventional antifungal therapy on candida colonization at 15 days (MD: 0.95, 95% CI: -0.28, 2.19, p = 0.13) and at the end of follow-up (MD: -0.17, 95% CI: -1.33, 0.98, p = 0.77). The pooled two studies revealed relatively better efficacy of adjunctive use of PDT with antifungal therapy on candida colonization compared to antifungal therapy alone at 15 days (MD: -6.67, 95% CI: -15.15, 1.82, p = 0.12), and at the end of follow-up (MD: -7.14, 95% CI: -19.78, 5.50, p = 0.27). Additionally, the results revealed comparable efficacy of PDT and topical antifungal therapy on the clinical outcomes. Conclusions PDT might be considered a viable option for DS either as an adjunct or as an alternative to the topical antifungal medications. Further studies with adequate sample sizes and standardized PDT parameters are warranted.